2020
DOI: 10.1111/ane.13323
|View full text |Cite
|
Sign up to set email alerts
|

Eslicarbazepine acetate in post‐stroke epilepsy: Clinical practice evidence from Euro‐Esli

Abstract: Stroke is a common cause of epilepsy, accounting for 11% of all epilepsy cases and 55% of newly diagnosed seizures in the elderly population. 1 Moreover, the relationship between stroke and epilepsy appears to be bidirectional, since middle-aged and elderly patients with newly diagnosed epilepsy have a twofold to threefold increased risk of stroke within approximately 2 years of epilepsy onset. 2,3 Post-stroke seizures usually have a focal seizure semiology, with approximately one third of cases presenting wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…A more recent analysis of the etiology‐specific treatment response was done in a post hoc analysis of the Euro‐Esli study on patients all of whom were treated with eslicarbazepine acetate in mono‐ or polytherapy. In that study, patients with epilepsy due to stroke compared to all other causes of focal epilepsy had a significantly higher 50% responder rate; that is, >50% fewer seizures with eslicarbazepine acetate than before 13 . However, there is no reason to assume that specific ASMs are more or less efficacious in focal epilepsy of different etiologies.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A more recent analysis of the etiology‐specific treatment response was done in a post hoc analysis of the Euro‐Esli study on patients all of whom were treated with eslicarbazepine acetate in mono‐ or polytherapy. In that study, patients with epilepsy due to stroke compared to all other causes of focal epilepsy had a significantly higher 50% responder rate; that is, >50% fewer seizures with eslicarbazepine acetate than before 13 . However, there is no reason to assume that specific ASMs are more or less efficacious in focal epilepsy of different etiologies.…”
Section: Discussionmentioning
confidence: 93%
“…In that study, patients with epilepsy due to stroke compared to all other causes of focal epilepsy had a significantly higher 50% responder rate; that is, >50% fewer seizures with eslicarbazepine acetate than before. 13 However, there is no reason to assume that specific ASMs are more or less efficacious in focal epilepsy of different etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled trials showing the efficacy and tolerability of individual drugs such as eslicarbazepine acetate [ 87 ], gabapentin [ 88 ], levetiracetam [ 89 , 90 ], valproic acid, and other newer ASMs [ 91 ] are also sparse. However, the validity of these studies is limited by bias, placebo effect, regression to the mean, and other confounding factors.…”
Section: Management Of Post-stroke Epilepsymentioning
confidence: 99%
“…Eslicarbazepine (ESL), LCM, oxcarbazepine (OXC), perampanel (PER), and zonisamide are currently underinvestigated in PSE [38][39][40]. An exploratory pilot study showed that LCM was relatively effective in patients with epilepsy with cerebrovascular aetiologies, with high tolerability, assuming that appropriate care is taken regarding contraindications (most importantly, certain cardiac conduction disorders).…”
Section: Choice Of Antiseizure Medication In the Treatment Of Post-stroke Seizuresmentioning
confidence: 99%